Academic writing centers and the teaching of academic writing at colleges: Literature review - Daniel Ginting; Yusawinur Barella (Intelektual Pustaka Media Utama, 2022)
Although colleges have offered academic writing courses, many students still struggle with this writing ability. Their poor writing skills are also associated with a lack of teacher guidance The tasks given by teachers are sometimes beyond their capabilities. Students are not accustomed to writing long academic papers. As a result, they do not enjoy writing essays, and they are not confident in their writing skills. This research is intended to collect and analyze articles related to Academic Writing Courses and the teaching of academic writing at colleges. The design used is a literature review, articles are collected using search engines such as JStore, Academic One file, Sciencedirect, and Proquest. The criteria for the articles used are those published in 2008-2021. Based on the articles collected the result is that academic writing centers (AWC) does not guarantee better grades for the students. Instead, it is time to help them fulfill their needs: i) Becoming self-directed; ii) Independent writers; iii) Building the confidence of writers; and iv) Helping writers with advanced writing tasks.